Optimalisasi Pelayanan Publik Bidang Transportasi di Dinas Perhubungan Kabupaten Gorontalo - Sartika Malahika; Rusly Abdurrahaman Idji; Rifka S. Akibu; Dian Fitriani Karim (Jurnal Media Administrasi, 2025)
This study aims to examine and describe the extent to which the optimization of public services in the transportation sector is implemented by the Gorontalo Regency Transportation Agency. The approach used is qualitative research with descriptive methods, in order to deeply understand the practices of transportation policies at the regional level. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation of the activities and policies implemented. The results of the study indicate that the optimization of public services in the transportation sector has been taking place progressively based on three main indicators. First, service effectiveness is reflected in the implementation of regulations in accordance with the law, such as controlling private vehicles parked haphazardly to reduce congestion and routine inspections of public vehicles to ensure safety aspects. Second, efficiency is achieved through technical supervision of vehicles that are not roadworthy, including brake conditions, tire wear, and completeness of route permits, as part of efforts to reduce operational risks and improve service quality. Third, productivity increases through the use of digital technology in socialization activities and the provision of supporting infrastructure such as bus stops, terminals, adequate roads, and traffic signs. These findings indicate that the Gorontalo Regency Transportation Agency has implemented a transportation service optimization strategy that is adaptive and oriented to community needs.